Industry 5.0 in Informatics: Bibliometric Analysis of Human‑Centric Automation with Cross‑Country Collaboration and Funding Agency Mapping - Judijanto, Loso; Widuri, Ruri (Westscience Press, 2025)
This paper examines the conceptual and collaborative framework of Industry 5.0 in informatics, concentrating on the growing paradigm of human-centric automation. This research employs a bibliometric analysis of publications indexed in the Scopus database from 2016 to 2025 to investigate publication trends, thematic progression, international collaborations, and contributions from funding agencies. Data were examined using Bibliometrix (R) and VOSviewer to illustrate co-authorship, keyword co-occurrence, and institutional networks. The findings indicate that Industry 5.0 research is transitioning from a focus on technology issues—like automation and cyber-physical systems—to a comprehensive framework that prioritizes human-machine collaboration, sustainability, and ethical innovation. Principal theme clusters focus on artificial intelligence, the Internet of Things, ergonomics, and decision-making, constituting the intellectual foundation of human-centric informatics. European and Asian nations, notably Italy, the United Kingdom, India, and China, lead in scientific output, bolstered by robust institutional collaboration and varied funding mechanisms. The research offers novel perspectives on how informatics facilitates the shift towards human-centered industrial ecosystems, integrating engineering, data science, and social innovation. The results advance the theoretical framework of Industry 5.0 as a socio-technical system and provide practical recommendations for policymakers, researchers, and funding bodies in promoting sustainable and equitable digital transformation.